Risk factors for community-acquired pneumonia in children under five years of age in the post-pneumococcal conjugate vaccine era in Brazil: a case control study. Issue 1 (December 2016) - Fonseca Lima, Eduardo; Mello, Maria; Albuquerque, Maria; Lopes, Maria; Serra, George; Lima, Debora; Correia, Jailson
Abstract Background Pneumonia plays an important role in children's morbidity and mortality. In Brazil, epidemiological and social changes occurred concomitantly with the universal introduction of the 10-valent pneumococcal conjugate vaccine. This study identified risk factors for pneumonia following the implementation of a pneumococcal vaccination program. Methods A hospital-based, case-control study involving incident cases of pneumonia in children aged 1–59 months was conducted between October 2010 and September 2013 at a tertiary hospital in northeastern Brazil. The diagnosis of pneumonia was based on the World Health Organization (WHO) criteria. The control group consisted of children admitted to the day-hospital ward for elective surgery. Children with comorbidities were excluded. The risk factors for pneumonia that were investigated were among those classified by the WHO as definite, likely and possible. A multivariate analysis was performed including variables that were significant atp ≤ 0.25 in the bivariate analysis. Results The study evaluated 407 children in the case group and 407 children in the control group. Household crowding (OR = 2.15; 95 % CI, 1, 46–3, 18) and not having been vaccinated against the influenza virus (OR = 3.59; 95 % CI, 2, 62–4.91) were the only factors found to increase the likelihood of pneumonia. Male gender constituted a protective factor (OR = 0.53; 95 % CI, 0, 39–0, 72). Conclusion Changes on risk factors for pneumonia were most likely associated with the expansion of the vaccination program and social improvements; however, these improvements were insufficient to overcome inequalities, given that household crowding remained a significant risk factor. The protection provided by the influenza vaccine must be evaluated new etiological studies. Furthermore, additional risk factors should be investigated.